Cultivating Critical Thinking Skills in Early Childhood Through Riau Local Wisdom: A Systematic Review of Gurindam Dua Belas by Raja Ali Haji - Mohammad Fauziddin; Gunarti Dwi Lestari; Neni Mariana; Suryanti Suryanti (LPPI Yayasan Almahmudi bin Dahlan, 2026)
Critical thinking is a foundational skill for lifelong learning, and educators increasingly look to local wisdom and cultural resources to cultivate it from an early age. This systematic literature review examines how Gurindam Dua Belas, a didactic poem embodying the local wisdom (kearifan lokal) of the Riau Malay community and authored by Raja Ali Haji, can be used to stimulate critical thinking in early childhood (children aged approximately 4–6 years). Following the PRISMA 2020 protocol, records were retrieved from Google Scholar using the keywords “Gurindam Dua Belas,” “critical thinking,” “early childhood education,” and “local wisdom,” covering publications from 2016 to 2026. After identification, screening, and eligibility assessment, 10 articles met the inclusion criteria and were analyzed using a thematic synthesis approach. The review finds that the twelve sections of Gurindam Dua Belas embed six recurring value themes—Islamic and aqidah values, social and moral values, the value of beneficial action, ethical values, and leadership and governance values—that can be translated into reflective questioning and interpretative reading activities to prompt children to identify problems, weigh evidence, and evaluate consequences, the core operations of critical thinking. These findings suggest that culturally embedded local wisdom literature offers early childhood educators a low-cost, contextually meaningful complement to imported thinking-skills curricula, provided teachers are given concrete pedagogical guidance for translating gurindam verses into age-appropriate dialogic activities. Future classroom-based intervention studies are needed to test these pedagogical translations directly with children.